PENGARUH LEVERAGE, FIRM SIZE, PROFITABILITY DAN LIQUIDITY TERHADAP CORPORATE CASH HOLDING - Hansen Kurniawan, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2020)
This thesis is made to examine the effect of leverage, firm size, profitability and leverage towards corporate cash holding. The sample used in this study consist of 63 manufacturing companies in basic industry and chemicals, consumer goods industry, and miscellaneous industry listed on Indonesia Stock Exchange from 2016-2018. This study used Eviews version 9 software to process data. The result of this study is firm size, profitability and liquidity have positive significant effect on corporate cash holding while leverage have no significant effect on corporate cash holding.